GRET Appropriate Technologies for Developing Countries - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
The Group for Research and Technological Exchange (GRET) was created ten years ago by french development workers who wanted to work outside the rigid structure of established development programmes. They chose to concentrate on scientific and...